Badan Hukum Publik, Wanprestasi, Perbuatan Melawan Hukum, Kepailitan - THOMAS YANUAR JOKO PRABOWO, 031411133005 (2018)
In the business format, a franchise is a business arrangement in which a grant of right to use a trade name by the Franchisor to an independent party or Franchisee to sell the product or service in accordance to the agreement. 7-Eleven Inc. is a Franchisor which sells its trade name in the form of convenience stores around the world, which began to have a presence in Indonesia on 2009. Throughout its operation, of 7-Eleven Indonesia experienced many obstacle. This makes 7-Eleven Indonesia accepts the risk. Such risk is the Franchisee’s ability to defend their different business which may make the Franchisee bankrupt. This thesis uses normative legal research methods by examining and interpreting legal facts that have been raised and associated with relevant legal materials. The conclusion of this thesis is that there are legal consequences of the bankruptcy of the Franchisee that occurred both in general and in a more specific case, there are also various legal efforts that can be taken from the circumstances of Franchisee’s bankcruptcy by the Franchisor